Ligneous Periodontitis: A Molecularly Confirmed Case of Type I Plasminogen Deficiency - Sarioğlu, A.; Ugurlu, K.; Karaman, M.; Karakaya, T.; Kirtiloǧlu, T.; Zengin, A.Z. (Medicina Oral S.L., 2025)
Congenital plasminogen (PLG) deficiency is an exceptionally uncommon hereditary disease associated with biallelic pathogenic / likely pathogenic variants in the PLG gene. Ligneous periodontitis (LP) is a rare disorder that can occur as a result of a lack of plasminogen. It is defined by the presence of lobulated, membranous, and ulcerated masses in the gums, as well as significant damage to the surrounding bone. This case report presents the diagnosis, treatment, and follow-up outcomes of a 23-year-old male patient who referred to our clinic with a complaint of widespread gingival enlargement. We identified a novel c.2087G>C (p.Arg696Pro) variant with a known variant detected in a compound heterozygous state in PLG confirming the molecular etiology. This case report emphasizes the importance of dentists identifying oral manifestations of various systemic diseases. Careful examination of such findings and the timely referral of patients to appropriate specialists for diagnosis and treatment are of critical significance. © Medicina Oral S. L. C.I.F. B 96689336
Keywords: Genetic Confirmation; Histopathological Diagnosis; Ligneous Periodontitis; Plasminogen Deficiency